PEMBUATAN MEDIA PERTUMBUHAN BAKTERI ESCHERICHIA COLI DENGAN MENGGUNAKAN UMBI UBI JALAR PUTIH IPOMOEA BATATAS - Ita Hasanah Br Karo; Rasyidah Rasyidah; Rizki Amelia Nasution (Jurnal Teknik dan Science, 2024)
Nutrient Agar (NA) is a growth medium for heterotrophic microorganisms made from meat extract, peptone and agar, but commercially it is relatively expensive. As an alternative, researchers innovated using white sweet potatoes (Ipomoea batatas) which are rich in carbohydrates, protein, fat and natural fiber as a growth medium for Escherichia coli bacteria. The aim of this research is to examine the use of white sweet potato flour as a growth medium for Escherichia coli bacteria, and compare it with a medium that is added with meat broth. This research used the experimental research method twice with three repetitions of sweet potato flour, namely 10gr (w/v), 15gr (w/v), 20gr (w/v) and NA control. After conducting research on white sweet potato flour, it was found that the water content test results met the standards of around 8.56–9.66%. The panelists' organoleptic test stated that white sweet potato flour had a smooth texture, yellowish white color, slightly sweet aroma. The solubility test proved that white sweet potato flour does not dissolve in water, and the pH test showed a value of 6.8, the percentage of carbohydrates contained was 74.32%, and protein 1.36%. The results obtained by the number of bacterial colonies with the best treatment without broth were F3 (20 gr white sweet potato flour) 25.5 x 106 CFU and the best treatment with the addition of broth was F2 (sweet potato flour + 15 gr broth) 28.7 x 106 while the NA control showed results of 25.6 x 106 CFU. It can be concluded that white sweet potato flour meets all test standards so that it can be used as an alternative growth medium for bacteria, especially Escherichia coli.